A controllable heterogeneous structure and electromagnetic wave absorption properties of Ti2CTx MXene. Issue 30 (20th July 2017) - Li, Xinliang; Yin, Xiaowei; Han, Meikang; Song, Changqing; Sun, Xinnan; Xu, Hailong; Cheng, Laifei; Zhang, Litong
Abstract : Herein, Ti2 CT x MXene and its derivatives with various heterogeneous structures were constructed via etching and a facile oxidation treatment. Abstract : Herein, Ti2 CT x MXene and its derivatives with various heterogeneous structures were constructed via etching and a facile oxidation treatment. The effect of different oxidation conditions on their structural evolution and phase composition was studied in detail. Compared with that of pristine Ti2 CT x MXene, the improvement in the electromagnetic wave absorption capability of the as-prepared Ti2 CT x /TiO2 and C/TiO2 nanocomposites was attributed to their enhanced polarization loss and stronger conductivity loss. The enhanced polarization loss is caused by the generated heterogeneous interfaces and higher specific surface area, and the stronger conductivity loss is due to the completely exfoliated carbon layers. Additionally, the remaining multilayered structure after exfoliation of the carbon layers favors energy dissipation. The C/TiO2 nanocomposites attain a minimum reflection coefficient of −50.3 dB at 7.1 and 14.2 GHz, and an effective absorption bandwidth of 4.7 GHz (covering the whole X-band) with a matching thickness of 2.1 mm; this indicates their excellent electromagnetic wave absorption properties. We believe that these nanocomposites with a heterogeneous structure also hold great promise for application in the fields of photocatalysis, lithium batteries, water purification, etc.